Farmacocinética populacional e toxicidade do sulfato de magnésio na pré-eclampsia - Costa, Tatiana Xavier da (2019)
Background: Magnesium sulfate (MgSO4) is the drug of choice to treat seizures in preeclampsia (PE) Despite the wide use, the therapeutic range ranges from 2.0-3.5 mmol/L. Objectives: To develop a population pharmacokinetic (PK) model of MgSO4 in preeclampsia, evaluating the impact of covariates in its pharmacokinetics,and to estimate the incidence of adverse drug reactions (ADR) in high-risk pregnancy and risk factors of RAM. Methods: Prospective cohort of patients with PE enrolled from June 2016 to February 2018 in use of MgSO4. Serum magnesium concentrations were obtained from 109 patients who received 4 g intravenously of MgSO4 and subsequent infusion of 1 g/h for 24 hours. Blood samples were obtained before administration and after 2, 6, 12 and 18 hours of the initial dose. Population pharmacokinetic parameters of MgSO4 (clearance, volume of distribution, time of half life) were estimated using the Monolix software ® 2018 Suite (Lixoft ®, Antony, France). A pharmacokinetic model including demographic, clinical and laboratory covariates of patients was developed. For the identification of ADR, 607 patients hospitalized in the ICU were evaluated daily through active search by pharmaceutical anamnesis, medical chart review and interviews with the healthcare team. Suspected ADR were classified about causality with Naranjo’s algorithm. Univariate and multivariate logistic regression was used to identify risk factors of ADR. Written informed consent was obtained from all patients. Results: The PK model that best adjusted the data was the one compartment with linear elimination. The population clearance was 1.38 L/h, the volume of distribution was 13,3 L and the baseline magnesium concentration was 0,77 mmol/L (1,87 mg/dL). The covariates body weight and serum creatinine have shown a statistically significant association with magnesium clearance and volume of distribution, respectively. Regarding ADR in high-risk pregnancy, one or more ADR were observed in 27.2%, the most implicated drug was MgSO4 (25.2%) with 44.5% of patients administered MgSO4experiencing ADR, most often somnolence (68.6%), absent patellar reflex (21.6%) and hypotension (9.8%). Risk factors of ADR were blood pressure (adjusted odds-ratio (aOR) 1.02), haemoglobin level (aOR 1.21) and body temperature (aOR 0.71). Conclusion: The pharmacokinetics of MgSO4 in pregnant women with PE are significantly affected by serum creatinine and body weight. Pregnant women with PE and higher body weight have a higher volume of distribution and, consequently, a lower elimination rate of MgSO4. Pregnant women with PE and higher serum creatinine value show lower clearance and, therefore, lower magnesium sulfate elimination rate. ADR affect about one fourth of high-risk pregnancies, mainly due to MgSO4administrations. High blood pressure, lower body temperature, and high haemoglobin concentration on admission were associated with increased risk of ADR.